Noisy neighbors - Moon, Nicola; Million, Liz (London : Kingfisher, 2003)
Contains two simple stories about animal neighbors who compromise in order to get along with one another.
Noisy neighbors -- Just in time.
3.0
K-3.
K-3
Keywords: Animals -- Fiction; Neighbors -- Fiction; Animals -- Fiction; Neighborhoods -- Fiction